Correlation of Dietary Intake and Body Composition with Circulating Betatrophin Levels in Overweight Young Women - Mayesti Akhriani; Alifiyanti Muharramah; Afiska Prima Dewi; Wimba Widagdho Dinutanayo; Meti Kurniawati (Journal of Nutrition Explorations, 2026)
Overweight in women of reproductive age increases the risk of insulin resistance. Betatrophin, a hormone related to lipid and glucose metabolism, is considered a potential metabolic associated with insulin resistance risk. Despite increasing evidence linking betatrophin with insulin resistance and obesity, data regarding its association with dietary intake, body composition, and lipid profile among young overweight women in Indonesia remain limited. This study aimed to examine the correlation between dietary intake, physical activity, body composition, lipid profile, and menstrual cycle with betatrophin levels in overweight women aged 20–30 years. A cross-sectional study was conducted on overweight participants within this age group. Dietary intake was collected using repeated 24-hour recalls, while physical activity and menstrual patterns were obtained through questionnaires. Body composition, including fat and muscle mass, was measured using bioelectrical impedance analysis (BIA). Serum lipid profile and betatrophin concentrations were analyzed by ELISA. Spearman’s correlation test was applied to determine the relationships among variables. Betatrophin levels showed positive correlations with energy intake (r=0.566; p=0.0001) and fat intake (r=0.366; p=0.028). Fat intake and body fat percentage were positively correlated with total cholesterol and LDL, while muscle mass showed negative correlations with both. Although women with irregular menstrual cycles tended to have higher betatrophin levels, the difference was not significant. These findings suggest that dietary fat, energy intake, and body composition correlated to metabolic markers related to insulin resistance risk in overweight young women